2019
DOI: 10.1002/art.41024
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocytes in Chronic Periaortitis: A Novel Mechanism Linking Inflammation and Fibrosis

Abstract: Objective Chronic periaortitis (CP) is a rare disease characterized by periaortic and periiliac fibroinflammatory tissue. The pathogenic mechanisms leading to tissue accumulation and activation of fibroblasts are unclear. This study was undertaken to explore the role of fibrocytes, circulating precursors of tissue fibroblasts, in patients with CP. Methods We studied 44 patients with newly diagnosed CP and 30 healthy controls. Circulating fibrocytes were identified as Col1+CD45+ cells using flow cytometry. Retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Another study, however, examined 44 patients with chronic periaortitis, one of the subtypes of IgG4-RD, and demonstrated the elevated level of CXCL12 and dominant infiltration of GATA3 + Th2 cells. This novel finding indicates CXCL12 might drive fibrocytes accumulation and Th2 differentiation ( 40 ).…”
Section: Adaptive Immunitymentioning
confidence: 89%
“…Another study, however, examined 44 patients with chronic periaortitis, one of the subtypes of IgG4-RD, and demonstrated the elevated level of CXCL12 and dominant infiltration of GATA3 + Th2 cells. This novel finding indicates CXCL12 might drive fibrocytes accumulation and Th2 differentiation ( 40 ).…”
Section: Adaptive Immunitymentioning
confidence: 89%
“…The IgG4 subclass of antibodies is expressed in alternative Th2 environments characterized by high levels of IL-10 ( 21 ). Furthermore, when an enhanced Th2 signal is observed, cytokines related to Th2 signaling, such as IL-10 and IL-13 are found to be elevated ( 22 ). It is known that Th2-skewed responses favor fibrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of lung fibrosis, it has been shown that human fibrocytes migrate in response to SDF-1/CXCL12 and localize to lungs if injected in bleomycin-treated animals ( Phillips et al, 2004 ). An increase in the number of collagen-positive fibrocytes was detected in chronic periaortitis patients, both in peripheral blood and in the affected tissue ( Nicastro et al, 2019 ). Similarly, in IgG4-RD patients, SDF-1/CXCL12 may recruit fibrocytes to affected organs, driving tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data draw attention to the role of SDF-1/CXCL12 as a mediator involved in recruiting circulating fibrocytes to the inflamed tissue in chronic periaortitis, a fibrotic disorder in the spectrum of IgG4-RD ( Nicastro et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%